Discontinuation of Nucleos(t)ide Analog treatment in HBeAg-Negative Non-Cirrhotic Chronic Hepatitis B Patients: Real-Life Data of 20 Years - Mete, Bilgül; Kaya, Sibel Yıldız; Kaya, Abdurrahman; Kurt, Ahmet Furkan; Bayramlar, Osman Faruk; Karaali, Rıdvan; Balkan, İlker İnanç and Yemişen, Mücahit and Özaras, Reşat and Saltoğlu, Neşe and et al. (Turkish Journal of Gastroenterology, 2023)
Background/Aims: Discontinuation of nucleos(t)ide analog is controversial in HBeAg-negative chronic hepatitis B patients not achieved HBsAg loss. We aimed to evaluate re-treatment rates and risk factors in non-cirrhotic HbeAg-negative chronic hepatitis B patients for whom nucleosi(t)ides analogs were discontinued. Materials and Methods: Demographic, clinical, and laboratory data before and at the end after discontinuation of nucleos(t)ide analogs were collected retrospectively. Results: Seventy-two patients followed up between January 2000 and December 2019 were included; 43 were male, with a mean age of 46.3 (±10.8). Baseline median alanine aminotransferase (ALT) and hepatitis B virus DNA levels were 55.5 IU/L and 465 925 IU/mL, respectively. The median histologic activity index was 5.5 and the fibrosis score was 2. The median duration of treatment and consolidation therapy were 59 and 56 months, respectively. The median follow-up time after discontinuation of treatment was 55 months. Among 56 patients eligible for evaluation according to proposed re-treatment criteria, 29 (51.7%) patients were re-treated. The median time for relapse was 11 months. Re-treatment was significantly common in males (P = .034) and patients treated with tenofovir/entecavir (P = .04). Baseline hepatitis B virus DNA and levels of ALT, aspartate aminotransferase (AST) at the third and sixth months of treatment and at the end of treatment were statistically significantly higher in re-treated patients. A cutoff value of ≥405 000 IU/L for hepatitis B virus DNA discriminated patients for re-treatment. HBsAg was lost permanently in 2 non-re-treated patients. Conclusion: In resource-limited areas where follow-up of HBsAg or other markers is not possible, nucleos(t)ide analog discontinuation can be considered in patients in the early stage, with low baseline hepatitis B virus DNA and ALT levels, after a long consolidation therapy. Cite this article as: Mete B, Yıldız Kaya S, Kaya A, et al. Discontinuation of nucleos(t)ide analog treatment in HBeAg-negative non-cirrhotic chronic hepatitis B patients: Real-life data of 20 years. Turk J Gastroenterol. 2023;34(11):1163-1170.